Women’s ownership of land and the time allocation decisions of spouses in rural farm households in Peru - Durán Fernández, Rosa Luz (2018)
A number of analytical and qualitative case studies have documented the importance of formal land ownership for women’s economic security and the improvement of their positions within their households (Deere and León 2001a; Deere and Doss 2006; Abraham, Gaspart, and Stevens 2005; Agarwal 1994, 2003). This expectation is rooted in the assumption that female land rights will increase women’s bargaining power.1 Redistributions of property rights to land towards women via the formal titling of their land or via the inclusion of their names as co-proprietors in deeds previously held by their husbands alone, the theory predicts, can affect the distribution of other household resources and participation in paid employment. This paper challenges the conventional wisdom about the bargaining power hypothesis, which would make us expect a more equal distribution of domestic and market activities between the spouses that share ownership rights over the land they live in and work on. My main argument is that the impact of women’s land ownership on wives and husbands’ time allocation outcomes is heterogeneous and contingent upon size of the farm as well as upon the broader social and regional framework.